Impact of the morphology of TiO 2 films as cathode buffer layer on the efficiency of inverted-structure polymer solar cells - Wiranwetchayan O. (2014)
Semiconducting metal-oxide TiO 2 films were deposited on FTO substrates via a sol-gel method to fabricate inverted polymer solar cells. The pore size of the TiO 2 films was effectively controlled by using the sols different in stirring time. The solar cell was constructed with a fullerene derivative interlayer and a photoactive mixture of poly(3-hexylthiophene) (P3HT) and phenyl-C61-butyric acid methyl ester (PCBM) coated on the TiO 2 films, which were purposely fabricated to have different porosity, referred as dense film, mesoporous film, and macroporous film in this paper. The highest efficiency, ~3.4%, was achieved on the cell with mesoporous film as the cathode buffer layer. It was proposed that, compared with the case of dense film, the mesoporous film leading to power conversion efficiency enhancement resulted from the efficient charge separation introduced by increasing the interface area between an active layer and metal oxide films and thus lowering the recombination rate happened to the excited electrons with holes in the polymer. The cell with macroporous film showing a much low efficiency is attributed to electron trapping during the transport in large grains, leading to lowly efficient electron collection.